Agronomic Investigation of Spray Dispersion of Metal-Based Nanoparticles on Sunflowers in Real-World Environments - Ernst, Dávid; Kolenčík, Marek; Šebesta, Martin; Ďurišová, Ľuba; Ďúranová, Hana; Kšiňan, Samuel; Illa, Ramakanth; Safarik, Ivo; Černý, Ivan; Kratošová, Gabriela; Žitniak Čurná, Veronika; Ivanič Porhajašová, Jana; et al. (Plants (Basel, Switzerland), 2023)
In environmental and agronomic settings, even minor imbalances can trigger a range of unpredicted responses. Despite the widespread use of metal-based nanoparticles (NPs) and new bio-nanofertilizers, their impact on crop production is absent in the literature. Therefore, our research is focused on the agronomic effect of spray application of gold nanoparticles anchored to SiO2 mesoporous silica (AuSi-NPs), zinc oxide nanoparticles (ZnO-NPs), and iron oxide nanoparticles (Fe3O4-NPs) on sunflowers under real-world environments. Our findings revealed that the biosynthetically prepared AuSi-NPs and ZnO-NPs were highly effective in enhancing sunflower seasonal physiology, e.g., the value of the NDVI index increased from 0.012 to 0.025 after AuSi-NPs application. The distribution of leaf trichomes improved and the grain yield increased from 2.47 t ha-1 to 3.29 t ha-1 after ZnO-NPs application. AuSi-NPs treatment resulted in a higher content of essential linoleic acid (54.37%) when compared to the NPs-free control (51.57%), which had a higher determined oleic acid. No NPs or residual translocated metals were detected in the fully ripe sunflower seeds, except for slightly higher silica content after the AuSi-NPs treatment. Additionally, AuSi-NPs and NPs-free control showed wide insect biodiversity while ZnO-NPs treatment had the lowest value of phosphorus as anti-nutrient. Contradictory but insignificant effect on physiology, yield, and insect biodiversity was observed in Fe3O4-NPs treatment. Therefore, further studies are needed to fully understand the long-term environmental and agricultural sustainability of NPs applications.
Keywords: foliar application; sunflower yield; plant physiology; insect biodiversity assessment; seeds quality; iron oxide; nanofertilizers; silica; zinc; gold